PENGARUH KOREAN WAVE, BRAND AMBASSADOR DAN BRAND AWARENESS TERHADAP BRAND IMAGE SERTA DAMPAKNYA PADA KEPUTUSAN PEMBELIAN (Survey Online Pada Pengguna Skincare Produk Scarlett Whitening Di Ciayumajakuning) - Nanda; Lili Karmela Fitriani (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
This study aims to find out the influence of the Korean Wave, brand ambassador, and brand awareness on the brand image, and its impacts on purchasing decisions of Scarlett Whitening products. The population in this study was at least 18 years old, live in Ciayumajakuning (Cirebon, Indramayu, Majalengka, and Kuningan), watched or listened to at least 3 dramas/films/songs, knew that Song Joong-ki is the brand ambassador of Scarlett Whitening, and buyer and consumer of Scarlett Whitening products. The research method used non-probability sampling with purposive sampling. The samples were 170 respondents. The statistical instrument used was Structural Equation Model Partial Least Square (SEM-PLS). Data processing used SmartPLS version 3. The results of the study showed that Korean Wave had no influence on brand image, while brand ambassador and brand awareness influence the brand image. Moreover, Korean Wave, brand ambassador, and brand awareness had no influence on buying decisions, while brand image influence the buying decision. Brand image can mediate brand ambassador and brand awareness, but a brand image cannot mediate Korean Wave.